The Effect of Using Silent Way Towards Students’ Vocabulary Mastery - Hamid Kasman; Hidra Ariza (Modality Journal: International Journal of Linguistics and Literature, 2023)
AbstractThis research was due to some problems, the 7th-grade students of MTsS PPM Diniyyah Pasia have a limited amount of vocabulary and the teacher used the conventional method where the students focused on listening to the explanation of the teacher. This research was about finding out the effect of using silent ways on students’ vocabulary mastery at the 7th grade in MTsS PPM Diniyyah Pasia. This research used experimental research. The researcher used a quasi-experimental design employing pre-test and post-test control designs. The population of this research was at the seventh grade of MTsS PPM Diniyyah Pasia. The sample was VII.2 which was treated as the experimental class and VII.4 was treated as the control class. The findings in this research showed that the t-obtained (-7.951) was lower than the t-table (-1.667). In other words,  the alternative hypothesis  (Ha) was accepted which means that there was a significant effect of using The Effect of Using silent ways on students‘ vocabulary ability. Then, the calculation of post-test of both classes showed that the experimental and control classes obtained (-4.587) were lower than t-table (-1.667). It can be concluded that the alternative hypothesis (Ha) was accepted which means that there is a significant difference between using silent way and using conventional technique. Thus, it can be concluded that the entire hypothesis is accepted. It is proved that the use of silent ways of learning vocabulary can help the students master the vocabulary well. Abstrak  Penelitian ini dilatarbelakangi oleh beberapa masalah, yaitu siswa kelas 7 MTsS PPM Diniyyah Pasia memiliki jumlah kosakata yang terbatas dan guru masih menggunakan metode konvensional di mana siswa hanya fokus mendengarkan penjelasan guru. Penelitian ini bertujuan untuk mengetahui pengaruh penggunaan metode silent way terhadap penguasaan kosakata siswa kelas 7 MTsS PPM Diniyyah Pasia. Penelitian ini menggunakan penelitian eksperimen. Peneliti menggunakan desain kuasi eksperimen dengan menggunakan desain kontrol pretest dan posttest. Populasi penelitian ini adalah siswa kelas VII MTsS PPM Diniyyah Pasia. Sampel penelitian ini adalah kelas VII.2 yang diperlakukan sebagai kelas eksperimen dan kelas VII.4 sebagai kelas kontrol.  Temuan dalam penelitian ini menunjukkan bahwa t-hitung (-7,951) lebih kecil dari t-tabel (-1,667). Sehingga hipotesis alternatif (Ha) diterima yang berarti terdapat pengaruh yang signifikan dari penggunaan metode silent way terhadap kemampuan kosakata siswa. Kemudian, perhitungan post-test kedua kelas yaitu kelas eksperimen dan kelas kontrol diperoleh t hitung (-4,587) lebih kecil dari t tabel (-1,667). Sehingga, hipotesis alternatif (Ha) diterima yang berarti terdapat perbedaan yang signifikan antara menggunakan metode silent way dan menggunakan metode konvensional. Jadi, dapat disimpulkan bahwa seluruh hipotesis diterima. Hal ini membuktikan bahwa penggunaan metode silent way dalam pembelajaran kosakata dapat membantu siswa menguasai kosakata dengan baik.